Omega-3 fatty acids: molecular weapons against chemoresistance in breast cancer - Vittoria Marchio; Giuseppina Augimeri; Catia Morelli; Adele Vivacqua; Cinzia Giordano; Stefania Catalano; Diego Sisci; Ines Barone; Daniela Bonofiglio (Cellular & Molecular Biology Letters)
Abstract Breast cancer is the most commonly diagnosed type of cancer and the leading cause of cancer-related death in women worldwide. Highly targeted therapies have been developed for different subtypes of breast cancer, including hormone receptor (HR)-positive and human epidermal growth factor receptor 2 (HER2)-positive breast cancer. However, triple-negative breast cancer (TNBC) and metastatic breast cancer disease are primarily treated with chemotherapy, which improves disease-free and overall survival, but does not offer a curative solution for these aggressive forms of breast cancer. Moreover, the development of chemoresistance is a major cause of therapeutic failure in this neoplasia, leading to disease relapse and patient death. In addition, chemotherapy’s adverse side effects may substantially worsen health-related quality of life. Therefore, to improve the outcome of patients with breast cancer who are undergoing chemotherapy, several therapeutic options are under investigation, including the combination of chemotherapeutic drugs with natural compounds. Omega-3 (ω-3) polyunsaturated fatty acids (PUFAs), including docosahexaenoic and eicosapentaenoic acids, have drawn attention for their antitumoral properties and their preventive activities against chemotherapy-induced toxicities in breast cancer. A literature review was conducted on PubMed using keywords related to breast cancer, omega-3, chemoresistance, and chemotherapy. This review aims to provide an overview of the molecular mechanisms driving breast cancer chemoresistance, focusing on the role of ω-3 PUFAs in these recognized cellular paths and presenting current findings on the effects of ω-3 PUFAs combined with chemotherapeutic drugs in breast cancer management.